Rectangular Glass Optical Fiber for Transmitting Sunlight in a Hybrid Concentrator Photovoltaic and Daylighting System - Afshin Aslian; Kok-Keong Chong; Seyed Hassan Tavassoli; Chin-Joo Tan; Omid Badkoobe Hazave (International Journal of Photoenergy)
In this paper, we propose to use glass optical fibers with a rectangular cross-section for the application in a concentrator photovoltaic and daylighting system (CPVD) due to the unique characteristics of rectangular fibers with the capability to provide a uniform rectangular beam shape and a top-hat profile at the output. A mathematical model of rectangular optical fibers has been formulated in this study for different incident angles, and the results are compared with those of round optical fibers. Furthermore, the performance of the bundle of RGOFs is compared with that of the bundle of round optical fibers via simulation by using the ray-tracing method. The mathematical modelling and numerical simulation have demonstrated that the RGOF has advantages in terms of the improvement in relative transmission and reduction in energy leakage for the transmission through the optical fiber. The simulation result also shows that a higher flux of sunlight can be transmitted via the bundle of RGOFs as compared to the bundle of round optical fibers due to the higher coupling efficiency. The experiment results on the relative transmission in different incident angles for both round optical fibers and RGOFs have validated both the simulation and the mathematical modelling. The beam profile of our fabricated RGOF has also been measured via our laboratory facility. The flexibility test on the fabricated RGOF has been carried out to bend at a radius of 150 mm and twist at 90° at a fiber length of 2.2 m.